2018
DOI: 10.3390/su10020500
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review of the Evidence of the Impact of Surface Water Quality on Property Values

Abstract: Abstract:The desirability of living on or close to water is reflected in sometimes substantial property price premiums. Water quality has an important influence on property prices, since it impacts a water body's appearance, capacity to support wildlife, and recreational potential. As water quality continues to be altered by human use and activity, and in light of new threats posed by projected climate and associated environmental change, understanding the impact of changing quality on property prices, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 46 publications
0
13
0
1
Order By: Relevance
“…4 A full list of the studies is provided in Appendix A. Although it was published after the construction of the meta-dataset, the list of identified studies was compared to an extensive literature review by Nicholls and Crompton (2018), which provided additional assurance that our identified set of studies is comprehensive. The final meta-dataset is publicly available on the US Environmental Protection Agency s (EPA) Environmental Dataset Gateway.…”
Section: Identifying Candidate Studies and Inclusion Criteriamentioning
confidence: 99%
“…4 A full list of the studies is provided in Appendix A. Although it was published after the construction of the meta-dataset, the list of identified studies was compared to an extensive literature review by Nicholls and Crompton (2018), which provided additional assurance that our identified set of studies is comprehensive. The final meta-dataset is publicly available on the US Environmental Protection Agency s (EPA) Environmental Dataset Gateway.…”
Section: Identifying Candidate Studies and Inclusion Criteriamentioning
confidence: 99%
“…The eutrophication problem in the U.S. Northeast is widespread and is both ecologically and economically damaging (Liu et al, ; Merrill et al, ; Nicholls & Crompton, ). Many coastal embayments in the U.S. Northeast have been designated impaired as pertaining to section 303(d) of the Clean Water Act (Masschusetts Department of Environmental Protection (MassDEP) ; Cape Cod Commission, ).…”
Section: Introductionmentioning
confidence: 99%
“…Waterfront properties are typically more valuable compared to those on adjacent land due to easy access to swimming, boating, and shing. Poor water quality is known to affect both enjoyment and property values of waterfront property (Hjerppe et al, 2016;Nicholls & Crompton, 2018). Therefore, perceptions of algal blooms are modi ed by the risks of loss of value of their properties.…”
Section: Discussionmentioning
confidence: 99%